Management Systems (Book). - Bruns, William J.; Nielsen, Gordon L. (The Accounting Review, 1969)
Reviews the book, "Management Systems," by Thomas B. Glans, Burton Grad, David Holstein, William E. Meyers and Richard N. Schmidt.